Pengaruh Air Rebusan Daun Salam (Eugenia polyantha Wight) 100% dan Sodium Hipoklorit (NaOCl) 1% sebagai Desinfektan Terhadap Stabilitas Dimensi Hasil Cetakan Alginat - Mila Aditya Zeni; Dewi Kristiana; Dwi Warna Aju Fatmawati (Fakultas Kedokteran Gigi Universitas Jember, 2014)
A factor that should be considered in the use of alginate impression materials is cross-infection control,therefore the result of alginate mold should be disinfected using a chemical or natural materials, such as sodiumhypochlorite (NaOCl) 1%, and bay leaf boiling water (Eugenia polyantha Wight) 100% before gypsum filling.However, this can lead to changes in the dimensional stability on the result of the mold. The objective of this researchwas to determine the effect of the use of these materials as a disinfectant with flushing and immersing method fordimensional stability of alginate mold result. The type of this study was laboratories experimental with post test onlycontrol group design. Total sample is 24 samples of alginate mold result were devided in to 6 groups: 2 control groupsand 4 treatment groups using the flushing and immersing methods. Data were tabulated and analyzed with TwoWay Analiysis of variance (Anova) technique adjusted for multiple comparisons using Tukey's (HSD) method wasused. The result of the study shows that the immersing method gives more influences to the dimensional stability ofalginate mold result, but use flushing method and both disinfectant materials do not have a significant effect ondimensional changes of alginate mold result.